2022
DOI: 10.1111/anae.15873
|View full text |Cite
|
Sign up to set email alerts
|

Network meta‐analysis of the analgesic effectiveness of regional anaesthesia techniques for anterior cruciate ligament reconstruction

Abstract: Summary Anterior cruciate ligament reconstruction can cause moderate to severe acute postoperative pain. Despite advances in our understanding of knee innervation, consensus regarding the most effective regional anaesthesia techniques for this surgical population is lacking. This network meta‐analysis compared effectiveness of regional anaesthesia techniques used to provide analgesia for anterior cruciate ligament reconstruction. Randomised trials examining regional anaesthesia techniques for analgesia followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 135 publications
0
7
0
Order By: Relevance
“…However, a case report suggested that the ACB may lead to impaired sciatic nerve function [ 19 ]. In other studies, the analgesic effect of the ACB were modest and clinically unimportant [ 2 , 20 , 21 ], Therefore, we believe that a single ACB may have limitations in the clinical setting.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, a case report suggested that the ACB may lead to impaired sciatic nerve function [ 19 ]. In other studies, the analgesic effect of the ACB were modest and clinically unimportant [ 2 , 20 , 21 ], Therefore, we believe that a single ACB may have limitations in the clinical setting.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies have reported that block combined with obturator nerve or infiltration between popliteal artery and posterior genicular capsule results in better analgesia without affecting quadriceps muscle strength compared with single FTB [ 27 , 28 ]. In addition, Hussain N et al have shown that compared with other block techniques, regional anesthesia techniques targeting the distribution of femoral and sciatic nerves can provide the most consistent analgesic benefits [ 2 ]. This is also the direction of future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with FNB consumed less opioids in the PACU compared to patients allocated to ACB (median 3 [0, 21] vs. 15 [12, 42.5] oral MME, p = 0.004). However, on postoperative day 1, opioid consumption was similar between groups (median 2.5 [2, 4.8] vs. 2 [1,4] oral MME, p = 0.527. The OBAS score was comparable between groups on POD 0 and POD 1.…”
Section: Secondary Outcomesmentioning
confidence: 95%
“…The Society for Ambulatory Anesthesia advocates for the utilization of local installation analgesia as the primary approach, suggesting the adoption of adductor canal block or femoral nerve block only when local installation is not a feasible option [ 3 ]. In contrast, a recent published network analysis, suggests the consideration of a single injection femoral nerve block combined with a sciatic nerve block, or local infiltration analgesia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%